Existing tests vs. novel non-invasive assays for detection of invasive aspergillosis in patients with respiratory diseases. Issue 13 (5th July 2022) - Xiao, Wei; Du, Longyi; Cai, Linli; Miao, Tiwei; Mao, Bing; Wen, Fuqiang; Gibson, Peter Gerard; Gong, Deying; Zeng, Yan; Kang, Mei; Du, Xinmiao; Qu, Junyan; et al.
Abstract: Background: Although existing mycological tests (bronchoalveolar lavage [BAL] galactomannan [GM], serum GM, serum (1, 3)-β-D-glucan [BDG], and fungal culture) are widely used for diagnosing invasive pulmonary aspergillosis (IPA) in non-hematological patients with respiratory diseases, their clinical utility in this large population is actually unclear. We aimed to resolve this clinical uncertainty by evaluating the diagnostic accuracy and utility of existing tests and explore the efficacy of novel sputum-based Aspergillus assays. Methods: Existing tests were assessed in a prospective and consecutive cohort of patients with respiratory diseases in West China Hospital between 2016 and 2019 while novel sputum assays (especially sputum GM and Aspergillus -specific lateral-flow device [LFD]) in a case-controlled subcohort. IPA was defined according to the modified European Organization for Research and Treatment of Cancer/Mycoses Study Group criteria. Sensitivity and specificity were computed for each test and receiver operating characteristic (ROC) curve analysis was performed. Results: The entire cohort included 3530 admissions (proven/probable IPA = 66, no IPA = 3464) and the subcohort included 127 admissions (proven/probable IPA = 38, no IPA = 89). Sensitivity of BAL GM (≥1.0 optical density index [ODI]: 86% [24/28]) was substantially higher than that of serum GM (≥0.5 ODI: 38% [39/102]) ( χ 2 = 19.83, P < 0.001), serum BDG (≥70 pg/mL: 33% [31/95]) ( χ 2 = 24.65, P < 0.001), and fungal culture (33% [84/253]) ( χ 2 = 29.38, P < 0.001). Specificity varied between BAL GM (≥1.0 ODI: 94% [377/402]), serum GM (≥0.5 ODI: 95% [2130/2248]), BDG (89% [1878/2106]), and culture (98% [4936/5055]). Sputum GM (≥2.0 ODI) had similar sensitivity (84% [32/38]) (Fisher's exact P = 1.000) to and slightly lower specificity (87% [77/89]) ( χ 2 = 5.52, P = 0.019) than BAL GM (≥1.0 ODI). Area under the ROC curve values were comparable between sputum GM (0.883 [0.812–0.953]) and BAL GM (0.901 [0.824–0.977]) ( P = 0.734). Sputum LFD had similar specificity (91% [81/89]) ( χ 2 = 0.89, P = 0.345) to and lower sensitivity (63% [24/38]) ( χ 2 = 4.14, P = 0.042) than BAL GM (≥1.0 ODI), but significantly higher sensitivity than serum GM (≥0.5 ODI) ( χ 2 = 6.95, P = 0.008), BDG ( χ 2 = 10.43, P = 0.001), and fungal culture ( χ 2 = 12.70, P < 0.001). Conclusions: Serum GM, serum BDG, and fungal culture lack sufficient sensitivity for diagnosing IPA in respiratory patients. Sputum GM and LFD assays hold promise as rapid, sensitive, and non-invasive alternatives to the BAL GM test.